Đặc điểm Tân kiến tạo - Địa động lực hiện đại Thành phố Lào Cai - Túc, Nguyễn Đăng; Hướng, Nguyễn Văn (Vietnam Journal of Earth Sciences, 2012)
Summary Neotectonics and present-day geodynamics in the area of Lao Cai city The Lao Cai city has been strongly influenced by Neotectonic and present-day geodynamic activities that created and modified some prominent structures such as : the Posen uplift with uplifting rate ranging from 0.14 to 0.28 mm/yr ; the Con Voi Range with post-metamorphic exhumation rate 10 mm/yr at early stage and decreased by 0.15 mm/yr in the present-day ; and Lao Cai block with subsidence rate 0.26 mm/yr. Textural-tectonic geometry in the area is characterized by amygdule (pull - apart), parallel and horsetail types. Main faults have NW-SE direction dipping north-eastwardly with steeply dips (79 - 88°). Subsidiary faults have NW-SE and sub-longitudinal directions with steeply dips (68 - 88°). In Holocene epoch, the NW-SE faults have right lateral sense of slip with slip rate about 7.4 mm/yr ; and the sub-faults have reverse or normal sense of slip depending on their spatial distribution.